Effect of herbal medicine Bojungikgi-tang on gut microbiome and symptoms in anorexic patients with atopic dermatitis: a randomized controlled trial - Lee, Boram; Ko, Mi Mi; Ahn, You Mee; Park, Hyo-Ju; Jung, So Young; Jung, Hyun-A; Lee, Hesol; Kim, Pyung-Wha; Choi, Yujin; Han, Kyungsun; Shin, Sarah; Jung, Jeeyoun (Frontiers in Pharmacology, 2025)
IntroductionAtopic dermatitis (AD) is often associated with gastrointestinal symptoms, including anorexia and alterations in the gut microbiome. A traditional East Asian herbal medicine Bojungikgi-tang (BJT; Buzhongyiqi-tang in Chinese, Hochuekki-To in Japanese) has been commonly used to manage AD and anorexia. This study aimed to evaluate the effects and safety of BJT in anorexic patients with AD and to investigate its therapeutic mechanism through gut microbiome analysis.MethodsThe trial included 26 adults with AD and anorexia, randomized (1:1) into BJT or waiting list groups for 12 weeks, including 8 weeks of treatment and 4 weeks of follow-up. The severity of anorexia and AD was assessed using the Visual Analog Scale (VAS), SCORing of Atopic Dermatitis (SCORAD), and Dermatology Life Quality Index (DLQI). Serum cytokine concentrations were measured before and after treatment using a multiplex immunoassay. Fecal samples were collected before and after treatment, and 16S rRNA sequencing was performed to analyze the gut microbiota.ResultsThe BJT group showed a significant decrease in anorexia VAS scores compared to the waiting list group at 8 weeks. Only the BJT group showed significant improvements in SCORAD and DLQI scores compared to baseline, with effects maintained through follow-up. No serious adverse events related to BJT were reported. Among the serum cytokines, IL-1β significantly decreased only in the BJT group, while IL-4 and IL-17 significantly decreased in both groups, with a more pronounced reduction observed in the BJT group. After 8 weeks of BJT treatment, significant changes were observed in the gut microbiome, including alterations in the Gemella genus, Gemmiger formicilis, and Blautia_uc species.ConclusionBJT may improve symptoms of anorexia and AD without serious adverse events, potentially through modifications in the gut microbiota.Clinical Trial RegistrationThe study protocol was registered at the Clinical Research Information Service (KCT0006784, https://cris.nih.go.kr/cris/search/detailSearch.do?seq=21298&search_page=L).